Preoperative modified frailty index to predict surgical complications in endometrial cancer patients - Aroontorn Pichatechaiyoot; Sarayut Thannil; Sathana Boonyapipat; Rakchai Buhachat (Korean Society of Obstetrics and Gynecology, 2022)
Objective To assess the predictive value of the preoperative modified frailty index (mFI) for postoperative complications in endometrial carcinoma, evaluate risk factors associated with complications, and compare the predictive properties of the mFI with the American Society of Anesthesiologists (ASA) physical status classification. Methods A total of 364 patients with endometrial cancer who underwent primary surgery between January 2009 and December 2016 were examined. The prognostic value of mFI in predicting severe postoperative complications, assessed according to the Clavien-Dindo classification, was analyzed and compared with ASA status. The risk factors for adverse outcomes were determined using multivariate analysis. Results The 30-day postoperative surgical- or medical-related complication rate was 26.6%. The rates of postoperative complications were 1.3%, 8.8%, 12.2%, and 60.0% for mFI scores of 0, 1, 2, and ≥3, respectively (P<0.001). The odds ratios for predicting postoperative complications in patients with mFI scores of 1, 2, and ≥3 were 7.38, 10.59, and 114.75, respectively. In the multivariate analysis, the significant predictive factors for postoperative complications were mFI ≥1, body mass index (BMI) ≥30 kg/m2, and non-endometrioid cell type. At cut-off points of mFI ≥1 and ASA ≥2, both tools had similar sensitivities but mFI was more specific (sensitivities 92.9% vs. 100%; specificity 45.5% vs. 19.4%). Conclusion mFI provides a satisfactory predictive value for postoperative complications. Patients with an mFI score ≥1, a BMI ≥30 kg/m2, and a non-endometrioid subtype, are at risk of postoperative complications and should receive comprehensive preoperative and postoperative management.